Implication of variable characters for the taxonomy of Altiphylax stoliczkai (Steindachner, 1867) and Altiphylax yarkandensis (Anderson, 1872) (Reptilia: Gekkonidae) with comments on the ZSI ‘syntype’ of the latter taxon’ - Das, Sunandan; Raha, Sujoy; Mitra, Shibajee; Bag, Probhat (Zootaxa, 2017)
We studied the available specimens of Altiphylax stoliczkai (Steindachner, 1867) collected during the Second Yarkand Expedition (1873–74) by Ferdinand Stoliczka. During our study we found some characters that exhibit intrapopulational variation which were not reported in previously published works on this species. We also examined ZSI 3792, said to be the ZSI syntype of Altiphylax yarkandensis (Anderson, 1872) and provide comments on its taxonomy and true status. Based on our study of specimens of A. stoliczkai and comparison with the published description and photographs of the Natural History Museum (NHM) syntype of A.yarkandensis, we regard the former to be a junior synonym of A. stoliczkai.